2007
DOI: 10.3354/ab00006
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal of sea louse larvae from salmon farms: modelling the influence of environmental conditions and larval behaviour

Abstract: Sea lice are ectoparasitic copepods of farmed and wild salmonids that cost the global salmon aquaculture industry more than US $100 million annually and have been implicated as a contributing factor in the decline of wild salmonid populations in the North Atlantic region. A coupled hydrodynamics-louse-transport model including varying physical forcing and sea louse larval behaviour was developed, and used to investigate: (1) the dispersal of sea louse larvae from a point source in an idealized coastal inlet; (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
60
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 34 publications
5
60
0
Order By: Relevance
“…This correlation indicates that the gravid L. salmonis on the farmed salmon were an important source of sea louse larvae. Plankton surveys have suggested that larval Lepeophtheirus salmonis can be carried several kilometres landward from their source (McKibben & Hay 2004a, Penston et al 2004, and this suggestion is supported by numerical models (Asplin et al 2004, Murray & Gillibrand 2006, Gillibrand & Willis 2007. This implies that self-sustaining L. salmonis populations on farms (Tully 1989, Bron et al 1993a,b, Jackson et al 1997, Revie et al 2005) might be contributing to infestation pressure in the wider environment, not just in their immediate vicinity.…”
mentioning
confidence: 57%
“…This correlation indicates that the gravid L. salmonis on the farmed salmon were an important source of sea louse larvae. Plankton surveys have suggested that larval Lepeophtheirus salmonis can be carried several kilometres landward from their source (McKibben & Hay 2004a, Penston et al 2004, and this suggestion is supported by numerical models (Asplin et al 2004, Murray & Gillibrand 2006, Gillibrand & Willis 2007. This implies that self-sustaining L. salmonis populations on farms (Tully 1989, Bron et al 1993a,b, Jackson et al 1997, Revie et al 2005) might be contributing to infestation pressure in the wider environment, not just in their immediate vicinity.…”
mentioning
confidence: 57%
“…It is unlikely that the copepodids recovered at Stn H in Cycle 2, or anywhere within the Loch Torridon management area during the present study, were transported there from farms in neighbouring management areas as the closest ones are > 30 km distant. A 10-yer study of sea lice infection on sea trout on the west coast of Ireland indicated that lice could disperse up to between 25 and 30 km from farms (Gargan et al 2003), and most sea lice dispersal models do not predict larvae to travel > 30 km (Krkošek et al 2005, Murray & Gillibrand 2006, Gillibrand & Willis 2007, Amundrud & Murray 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Gillibrand & Willis (2007) mathematically demonstrated such a model for the dispersal of sea lice larvae under typical coastal environmental conditions (including tidal, riverine and wind-driven currents) and showed that inclusion of larval behaviour in the model best explained field observations of copepodite distribution. In addition, their hydrographic model showed how below the seaward freshwater current is an upstream mid-depth current that can transport larvae towards land and into estuaries (figure 1).…”
Section: Research Progress (A) Larval Dispersal and Transportmentioning
confidence: 99%